Synthesis of Starch-Based Ag2[Fe (CN)5NO] Nanoparticles for Utilization in Antibacterial and Wound-Dressing Applications - Yuting Lu; Anbazhagan Sathiyaseelan; Xin Zhang; Lina Zhang; Kiseok Han; Myeong Hyeon Wang (MDPI AG, 2024)
Bacterial infections can lead to the formation of chronic wounds and delay the wound-healing process. Therefore, it is important to explore safe and efficient antimicrobial agents that have wound-healing and biocompatible properties. In this study, novel starch-fabricated silver nitroprusside nanoparticles (S-AgNP NPs) were prepared for biocompatible wound-healing applications. The study showed that S-AgNP NPs are spherical, with an average size of 356 ± 22.28 d. nm and zeta potential of −27.8 ± 2.80 mV, respectively. Furthermore, the FTIR and XRD results showed that S-AgNP NPs have functional groups and crystal structures from the silver nitroprusside nanoparticles (AgNP NPs) and starch. Additionally, S-AgNP NPs showed excellent bacterial and biofilm inhibition on B. cereus (15.6 μg/mL), L. monocytogenes (15.6 μg/mL), S. aureus (31.3 μg/mL), E. coli (31.3 μg/mL) and S. enterica (62.5 μg/mL). Moreover, S-AgNP NPs promoted cell migration and proliferation at a concentration of 62.5 μg/mL compared to AgNP NPs. Meanwhile, S-AgNP NPs had good biocompatibility and low cytotoxicity compared to AgNP NPs. Therefore, this study provided new ideas for the development of wound-healing agents with bacteriostatic properties in chronic wounds.